Implementasi Kebijakan Sistem Zonasi Penerimaan Peserta Didik Baru (PPDB) Pada Tingkat SMP Negeri Di Kabupaten Karimun - Rena Marshella; Rumzi Samin; Okparizan Okparizan (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2023)
The purpose of this study is to find out and describe the Implementation of the Zoning System Policy for New Student Admissions (PPDB) at the Junior High School Level in Karimun Regency, especially at SMP Negeri 1 Karimun and SMP Negeri 4 One Cliif Roof. This study uses a qualitative descriptive method with primary and secondary data sources. The theory used in this study is the Van Metre Van Horn Theory with six indicators: policy measures or objectives, resources, implementing characteristics, attitudes/dispositions, inter-organisational communication, social environment, economy, and politics. The study's findings are as follows: (1) the size and objectives of the zoning system policy at SMP Negeri 1 Karimun and SMP Negeri 4 Satu Atap Tebing have been operating in accordance with the established regulations even though the standards of success are not appropriate. (2) HR has already established quantity and quality but there are still facilities such as classrooms that are damaged. (3) the executors comprehend and perform their duties in accordance with the rules in a strict and disciplined manner; and (4) there are still pros and cons from the community, so far the executors have been very elpful in implementing the zoning system. (5) There has been inter-organizational communication; nevertheless, posters and socialisation have not all been dispersed equally. 6) From a societal standpoint, the general populace still doesn't understand computers. It has been operating in accordance with its objectives from an economic and political standpoint. The study's findings indicate that the PPDB zoning system has been implemented at SMP Negeri 1 Karimun and SMP Negeri 4 One Cliif Roof Tebing in accordance with Permendikbud Regulation Number 1 of 2021 and the technical guidelines established by the Regent of Karimun Regency prior to the start of new student admissions.